2013
DOI: 10.1371/journal.pone.0052909
|View full text |Cite|
|
Sign up to set email alerts
|

Japanese Encephalitis Virus Activates Autophagy as a Viral Immune Evasion Strategy

Abstract: In addition to manipulating cellular homeostasis and survivability, autophagy also plays a crucial role in numerous viral infections. In this study, we discover that Japanese encephalitis virus (JEV) infection results in the accumulation of microtubule-associated protein 1 light chain 3-II (LC3-II) protein and GFP-LC3 puncta in vitro and an increase in autophagosomes/autolysosomes in vivo. The fusion between autophagosomes and lysosomes is essential for virus replication. Knockdown of autophagy-related genes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 45 publications
2
72
1
Order By: Relevance
“…In contrast to dengue virus, the autophagic vacuole shows no evidence of being the site of replication for JEV. However, this finding is not consistent with the experiments conducted by Jin et al [48] and Wang et al [49] , who stated that the accumulation of the autophagosome and the autophagosome-lysosome fusion are essential to promote JEV replication [47][48][49] . In addition to initiating autophagy, viral intrusion also affects the intermediate step of the event.…”
Section: Autophagy Induction and Intracellular Replication In Viral Ccontrasting
confidence: 81%
“…In contrast to dengue virus, the autophagic vacuole shows no evidence of being the site of replication for JEV. However, this finding is not consistent with the experiments conducted by Jin et al [48] and Wang et al [49] , who stated that the accumulation of the autophagosome and the autophagosome-lysosome fusion are essential to promote JEV replication [47][48][49] . In addition to initiating autophagy, viral intrusion also affects the intermediate step of the event.…”
Section: Autophagy Induction and Intracellular Replication In Viral Ccontrasting
confidence: 81%
“…Inappropriate activation of the antiviral response can lead to cytotoxicity and cell death (30). We and others have demonstrated an IFN-␤-mediated antiviral response during JEV infection (31)(32)(33)(34). Recent studies have shown that miRNAs, such as miR-146, miR-155, and miR-203, are involved in regulating type I IFN signaling (30,35).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Japanese encephalitis virus (JEV) has been shown to subvert autophagy as a viral immune evasion strategy. The mechanism may be similar to that used by HCV, since type I IFN activation is increased when JEV infects cells deficient in autophagy (77). Infection with JEV increases autolysosome formation in vivo, and this formation is essential for maximum virus production (77).…”
Section: Possible Connections Among Viruses That Benefit From Autophamentioning
confidence: 99%
“…The mechanism may be similar to that used by HCV, since type I IFN activation is increased when JEV infects cells deficient in autophagy (77). Infection with JEV increases autolysosome formation in vivo, and this formation is essential for maximum virus production (77). Is it not yet known if autophagic degradation is responsible for restriction of the immune response during JEV infection.…”
Section: Possible Connections Among Viruses That Benefit From Autophamentioning
confidence: 99%